Correction of the Elevated Blood Pressure in Patients Undergoing Robot-Assisted Radical Prostatectomy - A. S. Kazakov; K. B. Kolontarev; E. S. Gorelova; O. A. Grebenchikov (Общая реаниматология)
The aim of the study was to evaluate the role of urapidil hydrochloride for the management of abnormal cardiovascular response in patients undergoing robot-assisted radical prostatectomy (RARP).Material and methods. The total of 93 prostate cancer patients scheduled for elective RARP were included and randomized in two groups: urapidil (n=44) and standard anesthesia control group (n=49). Urapidil was used to control the elevated blood pressure intraoperatively. Central hemodynamic monitoring was performed at 5 steps of the surgery.Results. In the control group, the step 2 of the procedure was associated with elevated mean blood pressure (by 24.3%, P=0.045) and increased total peripheral vascular resistance (by 46.6%, P=0.011) compared with step 1, while in the urapidil group no significant changes in these parameters were found. In the urapidil group, the blood pressure was lower by 20.2% (P=0.047), afterload by 36.9% (P=0.02) vs the control group values, whereas the cardiac output was higher by 22.2% (P=0.043). Placing patient in the steep Trendelenburg position (step 3) resulted in a 22.4% increase in stroke volume (P=0.38) in the control group and a 19.2% increase in stroke volume (P=0.049) in the urapidil group compared with the previous step. Cardiac output in the urapidil group was higher by 34% (P=0.002) and blood pressure and vascular resistance were lower by 24.4% (P=0.031) and 45.7% (P=0.001), respectively, vs the control group. At steps 4 and 5, gradual stabilization of the hemodynamic parameters and peripheral vascular tone with significantly smaller differences between the groups were revealed.Conclusion. Urapidil was effective for maintaining central hemodynamic parameters in patients during robotic-assisted radical prostatectomy at step 2 of the procedure, avoiding blood pressure elevation at step 3 and significantly reducing the total peripheral vascular resistance compared with the control group.